Prostaglandin Reductase 2 Modulates ROS-Mediated Cell Death and Tumor Transformation of Gastric Cancer Cells and Is Associated with Higher Mortality in Gastric Cancer Patients - Yun-Chia Chang, Emily; Tsai, Shu-Huei; Shun, Chia-Tung; Hee, Siow-Wey; Chang, Yi-Cheng; Tsai, Yun-Chih; Tsai, Jaw-Shiun; Chen, Hsian-Ju; Chou, Jia-Wei; Lin, Shih-Yao; Chuang, Lee-Ming (The American journal of pathology, 2012)
Various prostanoids and peroxisome proliferator-activated receptor γ (PPARγ) ligands play an important role in gastric cancer. Previously, we demonstrated that prostaglandin reductase 2 (PTGR2) catalyzes the reduction of the PPARγ ligand 15-keto-PGE2 into 13,14-dihydro-15-keto-PGE2. Here, we present functional data and clinical relevance for the role of PTGR2 in gastric cancer. Using lentiviral technology in AGS and SNU-16 gastric cancer cell lines, we either down-regulated or overexpressed PTGR2. In vitro analysis showed that PTGR2 knockdown resulted in decreased proliferation rate and colony formation, and in vivo xenograft models showed slower growth of tumors. Mechanistically, PTGR2 knockdown induced cell death, altered mitochondrial function, and increased reactive oxygen species production, which led to activation of ERK1/2 and caspase 3, with increased Bcl-2 and suppressed Bax expression. PTGR2 overexpression showed the opposite outcomes. Clinically, immunopathological staining showed strong PTGR2 expression in the gastric tumor portion, relative to nearby nontumor portions, and its expression negatively correlated with survival of patients with intestinal-type gastric cancer. Finally, in contrast to PTGR2-overexpressing cells, PTGR2-knockdown cells were more sensitive to cisplatin and 5-fluorouracil. Taken together, our findings not only provide functional and mechanistic evidence of the involvement of PTGR2 in gastric cancer, but also provide clinical observations affirming the significance of PTGR2 in gastric cancer and suggesting that PTGR2-target based therapy is worth further evaluation.